(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
The current study focused on estimating the accumulation of some heavy metals (Lead Pb, Cadmium Cd, and Chromium Cr) in Swiss Chard and Parsley and its relationship with the quality of groundwater and soil in three agricultural areas in Ghat city: Al-Fayut, Al-Barkat, and Ghat. This study aimed to determine the levels of heavy metal pollution in these farms and evaluate their compliance with international standards (WHO), in addition to analyzing the relationship between soil, water, fertilizers, and the accumulation of these elements in plants. The study was conducted by collecting plant, water, and soil samples from the three farms, which were then analyzed using Atomic Absorption Spectroscopy (AAS) and an electrical conductivity meter. The results showed that Al-Fayut farm was the least polluted due to the use of pure groundwater and well-aerated sandy soil. Conversely, the Ghat farm showed the highest accumulation of heavy metals due to its proximity to waste and burning areas, while Al-Barkat farm showed intermediate levels. The study recommended the necessity of monitoring water and soil quality and avoiding the use of contaminated fertilizers to ensure the safety of agricultural products and protect public health.